Eavesdropping on Plant Volatiles by a Specialist Moth: Significance of Ratio and Concentration - Cha, Dong H. (Public Library of Science, 2011)
We investigated the role that the ratio and concentration of ubiquitous plant volatiles play in providing host specificity for the diet specialist grape berry moth Paralobesia viteana (Clemens) in the process of locating its primary host plant Vitis sp. In the first flight tunnel experiment, using a previously identified attractive blend with seven common but essential components (“optimized blend”), we found that doubling the amount of six compounds singly [(E)- & (Z)-linalool oxides, nonanal, decanal, β-caryophyllene, or germacrene-D], while keeping the concentration of other compounds constant, significantly reduced female attraction (average 76% full and 59% partial upwind flight reduction) to the synthetic blends. However, doubling (E)-4,8-dimethyl 1,3,7-nonatriene had no effect on female response. In the second experiment, we manipulated the volatile profile more naturally by exposing clonal grapevines to Japanese beetle feeding. In the flight tunnel, foliar damage significantly reduced female landing on grape shoots by 72% and full upwind flight by 24%. The reduction was associated with two changes: (1) more than a two-fold increase in total amount of the seven essential volatile compounds, and (2) changes in their relative ratios. Compared to the optimized blend, synthetic blends mimicking the volatile ratio emitted by damaged grapevines resulted in an average of 87% and 32% reduction in full and partial upwind orientation, respectively, and the level of reduction was similar at both high and low doses. Taken together, these results demonstrate that the specificity of a ubiquitous volatile blend is determined, in part, by the ratio of key volatile compounds for this diet specialist. However, P. viteana was also able to accommodate significant variation in the ratio of some compounds as well as the concentration of the overall mixture. Such plasticity may be critical for phytophagous insects to successfully eavesdrop on variable host plant volatile signals.